Detection Performance Improving Method Analysis of Infrared Imaging Seeker against Stealth Aircraft - Li Lijuan, Liu Ke, Xu Zhenya, Shi Xiaogang (Hangkong bingqi, 2024)
The emergence of stealth aircraft poses a challenge to the target detection capabilities of existing radar and infrared guided air-to-air missiles. Compared to the better radar stealth performance of stealth aircrafts, infrared guided air-to-air missiles have the advantage of anti stealth. However, some measures should be taken by the infrared seeker to improve its detection and recognition ability for stealth targets. In this paper, aiming to improve the ability of infrared imaging seeker to detect stealth targets, the infrared radiation characteristics of stealth aircraft are analyzed firstly. Then, based on the factors affecting the detection performance of infrared imaging seekers, various solution are proposed to improve the detection and recognition capabilities of infrared detection system for stealth aircraft, such as using dual color/multi band imaging detection, optimizing the working parameter design of infrared detection system, increasing imaging quality and scene adaptability in different environments, and adopting low signal-to-clutter ratio target detection and interception technology.